Effect of metal slots on the heating uniformity of multisource cavity microwave - Yin, Shumeng (Frontiers in Energy Research, 2023)
Microwave heating as a new type of heating has been widely used in numerous fields; however, microwave heating in multi-source cavity still poses several problems, including non-uniformity, low efficiency, restriction of the heating object, and "thermal runaway", thus limiting the application of microwave energy. This study adopts a method to place a slotted layer in the cavity such that the energy can be radiated uniformly to improve the heating uniformity. The distribution of the electric field in the cavity is optimized by changing the arrangement and size of the slots in the slot layer. The effects of the slot arrangements are elucidated, and experiments are performed to study the real-life application of the slot arrangements. The results show that these metal slots are effective in improving the uniformity and efficiency of multisource cavity heating.